2017
DOI: 10.1007/s10897-017-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

Referrals to Mental Health Services: Exploring the Referral Process in Genetic Counseling

Abstract: Genetic counselors (GCs) are trained to identify and attend to distress; however, GCs may have patients with distress better managed by mental health professionals (MHPs). To understand the GCs' role in mental health care, we explored patient cues prompting GCs to refer to MHPs and where GCs thought their expertise in managing patient distress ended. We recruited GCs who have referred a patient for mental health services within the last year to participate in an interview study. A twelve-question interview gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A recent study observed that genetic counsellors define their role regarding psychosocial problems as short term, referring counselees to mental health services when they perceive limited social support or significant anxiety related to a high-risk status or recent cancer diagnosis. 58 Psychological care after the test result receipt was associated to higher negative emotions, suggesting that more distressed counselees received psychological care or that this was ineffective in reducing negative emotions 2 months after the receipt of test result. Less than 15% of counselees received psychological care after testing, and among these, about 40%-60% of them had been referred by genetics clinicians depending on the country setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study observed that genetic counsellors define their role regarding psychosocial problems as short term, referring counselees to mental health services when they perceive limited social support or significant anxiety related to a high-risk status or recent cancer diagnosis. 58 Psychological care after the test result receipt was associated to higher negative emotions, suggesting that more distressed counselees received psychological care or that this was ineffective in reducing negative emotions 2 months after the receipt of test result. Less than 15% of counselees received psychological care after testing, and among these, about 40%-60% of them had been referred by genetics clinicians depending on the country setting.…”
Section: Discussionmentioning
confidence: 99%
“…Distress was strongly related to all domains of psychosocial problems 2 months after the receipt of the test result,32 48 highlighting the many facets underlying distress that may be targeted for counselling. The role of genetic clinicians, psychologists or psychosocial workers with regard to psychosocial problems specific to the genetic context is not clearly delineated 58. The effect of genetic testing on psychosocial problems related to hereditary predisposition concerns suggests that genetic clinicians played a main role in that domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…surrounding psychiatric disorders has provided tremendous insight to increase the efficacy of attending to behavioral healthcare needs for patients and recognizing necessity for referral (Austin & Honer, 2007;Cunningham et al, 2018;Hippman et al, 2013).…”
Section: Gc Research Regarding Psychosocial Concerns and Counselingmentioning
confidence: 99%